Age-related reweighting of visual and vestibular cues for vertical perception - Alberts, Bart B. G. T.; Selen, Luc P. J.; Medendorp, W. Pieter (Journal of neurophysiology, 2019)
As we age, the acuity of our sensory organs declines, which may affect our lifestyle. Sensory deterioration in the vestibular system is typically bilateral and gradual, and could lead to problems with balance and spatial orientation. To compensate for the sensory deterioration, it has been suggested that the brain reweights the sensory information sources according to their relative noise characteristics. For rehabilitation and training programs, it is important to understand the consequences of this reweighting, preferably at the individual subject level. We psychometrically examined the age-dependent reweighting of visual and vestibular cues used in spatial orientation in a group of 32 subjects (age range: 19–76 yr). We asked subjects to indicate the orientation of a line (clockwise or counterclockwise relative to the gravitational vertical) presented within an oriented square visual frame when seated upright or with their head tilted 30° relative to the body. Results show that subjects’ vertical perception is biased by the orientation of the visual frame. Both the magnitude of this bias and response variability become larger with increasing age. Deducing the underlying sensory noise characteristics, using Bayesian inference, suggests an age-dependent reweighting of sensory information, with an increasing weight of the visual contextual information. Further scrutiny of the model suggests that this shift in sensory weights is the result of an increase in the noise of the vestibular signal. Our approach quantifies how noise properties of visual and vestibular systems change over the life span, which helps to understand the aging process at the neurocomputational level. NEW & NOTEWORTHY Perception of visual vertical involves a weighted fusion of visual and vestibular tilt cues. Using a Bayesian approach and experimental psychophysics, we quantify how this fusion process changes with age. We show that, with age, the vestibular information is down-weighted whereas the visual weight is increased. This shift in sensory reweighting is primarily due to an age-related increase of the noise of vestibular signals.